Massive melanotic myocardial metastasis characterized by multiple cardiac imaging modalities - Karamitsos, T; Bull, S; Francis, J; Newton, J; Westaby, S; Neubauer, S; Myerson, S (2011)
Melanoma has a great propensity for cardiac involvement but most cases are diagnosed post-mortem. We present the case of a 67-year-old man with history of malignant melanoma who presented with increasing dyspnea, fatigue and peripheral edema. A large myocardial metastasis was identified on transthoracic echocardiography, and further characterized with cardiovascular magnetic resonance prior to surgery. © 2009 Elsevier Ireland Ltd. All rights reserved.